Acceptable Versus Straightforward Game Forms: An Example - Jordan, J. S. (Review of Economic Studies, 1983)
This paper is concerned with the design of non-cooperative game forms for economic decision problems. A decision problem is presented which admits non-dictatorial game forms with the following properties: Nash equilibria exist and all Nash equilibrium outcomes are Pareto optimal; or dominant strategies exist and all dominant strategy equilibria are Pareto optimal; but not both. This is, any (non-dictatorial) game form whose Nash equilibria are well behaved does not have dominant strategies, and any game form with well behaved dominant strategy equilibria must have at least one non-optimal non-dominant strategy Nash equilibrium.